Plant pathogens as introduced weed biological control agents: Could antagonistic fungi be important factors determining agent success or failure? - Den Breeyen, Alana; Lange, Claudia; Fowler, Simon V. (Frontiers in Fungal Biology, 2022)
Mycoparasitic interactions are common in nature, form part of the microbiota of plants, and are considered significant contributors to fungus-fungus antagonism. Mycoparasites kill plant pathogens, protect the plant from abiotic and biotic stressors, and reduce disease incidence and severity at the plant population level. Their exploitation as biocontrol agents in agriculture is well documented. However, mycoparasites may potentially affect classical fungal biocontrol agents of invasive weed species. Classical biological control, or biocontrol, of invasive weeds involves the intentional introduction of exotic, usually co-evolved plant pathogens and insects, for permanent establishment and long-term control of the target plant. Agent establishment, effectiveness, and safety are the critical elements for a successful weed biocontrol programme. The establishment and effectiveness of agents on the invasive plant often vary throughout the invaded range with about two-thirds of weed biocontrol agents failing to suppress their target weed. There are many documented reasons why weed biocontrol agents do not establish or are ineffective when they do, and the presence and accumulation of natural enemies in the invaded range is one of them. Endophyte-enriched, invasive weeds and those forming mutualistic associations with indigenous, native endophytes could explain the lack of consistency of some classical biological control introductions. However, another variable could be factored into the mix: mycoparasitism, where one fungus parasitises another, the natural enemies of the plant's natural enemies. In this review article, we introduce the concept of invasive weed biocontrol and the history of using plant pathogens as biocontrol agents. We discuss the success and failure of fungal agent programmes and delve into the patterns of success or failure, with a focus on the potential antagonistic role of endophytes and mycoparasites.